2021
DOI: 10.1111/jopr.13399
|View full text |Cite
|
Sign up to set email alerts
|

Hardness Development in Resin Composite Core Materials

Abstract: Purpose To investigate the hardness characteristics of 13 contemporary resin core materials. Materials and methods Specimens (n = 12) were fabricated using stainless steel molds with top surfaces of dual‐cure products photopolymerized while additional groups were allowed to self‐cure. Twelve Knoop hardness indentations 500 microns apart were obtained of photopolymerized top and bottom sample surfaces as well as the self‐cured sample surface with the mean recorded as the representative sample hardness. Testing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
2
0
0
Order By: Relevance
“…The high surface microhardness value obtained from S0M0 could be due to the higher level of DC upon light-curing or the higher proportion of rigid inorganic glass fillers of the material compared to other experimental formulations. The surface microhardness values obtained from the materials in the current study were similar to that of commercial materials reported in a published study [ 75 ]. The increase in surface hardness at four weeks may be due to the post-cure polymerization that could promote the cross-linking of the polymer network [ 75 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The high surface microhardness value obtained from S0M0 could be due to the higher level of DC upon light-curing or the higher proportion of rigid inorganic glass fillers of the material compared to other experimental formulations. The surface microhardness values obtained from the materials in the current study were similar to that of commercial materials reported in a published study [ 75 ]. The increase in surface hardness at four weeks may be due to the post-cure polymerization that could promote the cross-linking of the polymer network [ 75 ].…”
Section: Discussionsupporting
confidence: 87%
“…The surface microhardness values obtained from the materials in the current study were similar to that of commercial materials reported in a published study [ 75 ]. The increase in surface hardness at four weeks may be due to the post-cure polymerization that could promote the cross-linking of the polymer network [ 75 ]. The addition of hydrophilic fillers in the experimental materials may encourage water plasticization of the resin matrix.…”
Section: Discussionsupporting
confidence: 87%